Micro-Aerobic Pre-Treatment vs. Thermal Pre-Treatment of Waste Activated Sludge for Its Subsequent Anaerobic Digestion in Semi-Continuous Digesters: A Comparative Study - Alejandra Castillo; Eduardo Ortega-Martínez; Jhosané Pagés-Díaz; Silvio Montalvo; Cesar Huiliñir (Fermentation, 2022)
This article investigates methane production, organic matter removal, and energy by comparing micro-aerobic pre-treatment and thermal pre-treatment of waste-activated sludge (WAS). For micro-aerobic pre-treatment, WAS was pre-treated at 0.35 vvm (volume of air per volume of medium per minute) for 48 h. The data showed over a 30% increase in soluble Chemical Oxygen Demand (COD) and soluble proteins when this pre-treatment was applied. Then, the micro-aerobically pre-treated sludge was mixed with primary sludge and anaerobically digested in semi-continuous digesters with Hydraulic Retention Times (HRT) of 20, 15, and 10 days at 35 °C. We used two digesters as a control: one fed with a mixture of primary sludge (PS) and raw WAS; another fed with a mixture of PS and thermally pre-treated WAS. The results showed a better performance for the digester fed with micro-aerobically pre-treated sludge than the other two at all the HRT tested. The better performance is because of the solubilization of particulate organic matter, as shown at the reactor outlet. Energy consumption analysis showed that micro-aerobic pre-treatment required 32% more energy in a year than thermal pre-treatment. However, if sludge is pre-thickened in a similar way as performed for thermal pre-treatment, then the energy demand required by micro-aerobic pre-treatment is reduced by 41% concerning the thermal pre-treatment; nevertheless, more studies should be performed to verify that methane production and solid reduction advantages are maintained.